The trend to Joint Audit as an approach to Improve the Financial Reports Quality - An Applied Study – - حسين نشوان, اسكندر محمود (Journal of Economics and Administrative Sciences, 2017)
This study aimed at identifying the trend to applying the Joint Audit as an approach to improve the financial reports quality with all their characteristics (Relevance, Reliability, Comparability, Consistency), as well as enclose the difficulties that faced the auditors in the Gaza Strip in implementing the Joint Audit. In order to achieve the study aims, a measure was used to identify the trend to apply the Joint Audit and it was distributed to the study sample which is consisting of (119) individuals and retrieved thereof (99) valid for analysis, approximately (83.2%), (69) of them are Auditors, (30) financial managers and accountants. The researcher used the analytical descriptive method, and after analyzing the results, the study found that: There is a positive trend among all the sample individuals to apply the Joint Audit to improve the financial reports quality with their different characteristics (Relevance, Reliability, Comparability, and Consistency). As well as the existence of various difficulties are facing Joint Audit when applied it. According to the results, the study recommended that all denominations of the financial community should be encouraged to be interested in the trend to the Joint Audit because of the multiple positive effects, especially improving the financial reports quality, also working hard to find appropriate ways and methods to overcome the various difficulties that face the application of Joint Audit.  Thus contribute to increase completing the content of the information that contained in the financial reports.